Influence of ternary oxide additives on thermal conductivity of pressureless sintered Si3N4 - Kumar K.; Park Y.-J.; Kim M.-J.; Kim H.-N.; Jin Ma H.; Lee J.-W.; Ko J.-W. (My University, 2025)
Dense Si3N4 ceramic was fabricated by unimbedded pressureless sintering at 1650 °C with a short holding time of 1 h. The role of ternary oxide additives (Y2O3-MgO-SiO2 and Y2O3-MgO-ZrO2) on the phase and microstructure of Si3N4 and subsequently on thermal conductivity was examined. Y2O3-MgO-SiO2 additive facilitated α → β transformation better, whereas Y2O3-MgO- ZrO2 additive enhanced grain size (∼40 %), which led to higher thermal conductivity (>1.5 times, ∼50 W/m∙K). The influence of liquid phase viscosity on grain elongation was noteworthy. This study shows a cost-effective fabrication of highly-dense Si3N4 with desirable thermal conductivity. © 2022 Elsevier B.V.